Knockout.js building dynamic client-side web applications - Munro, Jamie (O'Reilly Media, 2015)
Use Knockout.js to design and build dynamic client-side web applications that are extremely responsive and easy to maintain. This example-driven book shows you how to use this lightweight JavaScript framework and its Model-View-ViewModel (MVVM) pattern.